(untitled) (Texas Journal of Medical Science, 2023)
This article explores the phraseology of French literature, which are unique phrases that reflect the cultural and historical aspects of France. The study focuses on analyzing and categorizing the most important phraseology in French literature, highlighting their linguistic and cultural significance. The research methods used in this study include a review of fiction texts and an analysis of the language structure and syntax of phraseology. The results section provides a complete list of the most widely used phraseology in French literature in combination with its meaning and cultural contexts. The discussion section examines the linguistic and cultural consequences of phraseology and their importance in modern French literature. The article concludes with suggestions for further research on the topic